Effects of mandatory military service on wages and other socioeconomic outcomes - Patrick A. Puhani; Margret K. Sterrenberg (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2021)
In this paper, we estimate the effects of mandatory military service by exploiting the post-cold war decrease in the need for soldiers causing a substantial number of potential conscripts not to be drafted into the German military. Specifically, using previously unavailable information on degree of fitness in the military's medical exam as a control variable, we test for the effects of mandatory military service on wages; employment; marriage/partnership status; and satisfaction with work, financial situation, health, family life, friends, and life in general. We find almost no statistically significant effects of this 6 to 9 month career interruption for young German men, with the exception of hourly wage, which shows a negative point estimate of -15 percent with a large confidence interval of between -30 and -0.2 percent. This interval estimate is consistent with previous findings for the United States, Denmark, and the Netherlands.
Keywords: J12; J24; J47; 330; career breaks; conscription; wages; employment; lifesatisfaction; natural experiment